2019
DOI: 10.1108/jic-01-2019-223
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital accounting in the age of integrated reporting: a commentary

Abstract: Intellectual capital accounting in the age of integrated reporting: A commentary AbstractPurpose: This commentary explores the extent to which the practice of integrated reporting (IR) in organisations can be a vehicle for furthering and sustaining the practice of accounting for intellectual capital (IC). It introduces the eight papers forming this special issue that demonstrates how organisations are developing practices at the nexus of IC and IR. Methodology:The commentary is a review of the eight papers, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 34 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…Companies that are willing to start the “integrated reporting journey” may in fact be encouraged to pay attention to their profitability, to the relevance that they pay to intangible resources, and to the size of their boards. This is consistent with the claim that some authors have done, advancing that intangible capitals have found a new life through IR (Abhayawansa, Guthrie, & Bernardi, ). Moreover, the buy‐in from the board has been identified as one of the fundamental steps (although not the only one) for a successful implementation (French Institute of Directors, ; IIRC, ).…”
Section: Discussion Of the Theoretical Practical And Policy Implicasupporting
confidence: 90%
“…Companies that are willing to start the “integrated reporting journey” may in fact be encouraged to pay attention to their profitability, to the relevance that they pay to intangible resources, and to the size of their boards. This is consistent with the claim that some authors have done, advancing that intangible capitals have found a new life through IR (Abhayawansa, Guthrie, & Bernardi, ). Moreover, the buy‐in from the board has been identified as one of the fundamental steps (although not the only one) for a successful implementation (French Institute of Directors, ; IIRC, ).…”
Section: Discussion Of the Theoretical Practical And Policy Implicasupporting
confidence: 90%
“…In relation to the determinants, Zuraida and Mulyany (2019), analysing 280 IPO prospectuses of Indonesian companies, found a positive and significant effect of year and firm size on ICD level. Other studies have analysed integrated reports (Abeysekera, 2013; Abhayawansa, Guthrie, & Bernardi, 2019; Beretta et al, 2019; Camodeca, Almici, & Sagliaschi, 2019; Casonato et al, 2018; Dumay, 2016; Dumay et al, 2019; Melloni, 2015; Terblanche & De Villiers, 2019; Veltri & Silvestri, 2015; Vitolla, Raimo, & Rubino, 2019b), but only two analysed the determinants of ICD. In this regard, Melloni (2015) highlighted how declining performance, the level of intangibles, and firm size influence the positive tone of ICD, while Beretta et al (2019) demonstrated the existence of a positive relationship between non‐financial performance and the optimistic tone of ICD.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…However, an environmental culture of an organization can refers to the set of values, organizational culture, assumptions, and symbols (Rehman, Kraus, Shah, Khanin, & Mahto, 2017), and consistent with Meijerink & Bondarouk (2018), an important relation exists between green HRM and organizational culture. Moreover, e-HRM that is vital part of IT system of Green Structural Capital, was found to have a relation with green practices of HRM (Alfaro-Navarro, López-Ruiz, & Peña, 2017;Akhtar, Ismail, Ndaliman, Hussain, & Haider, 2015;Abhayawansa, Guthrie, & Bernardi, 2019).…”
Section: Green Intellectual Capitalmentioning
confidence: 99%